[OP.3C.06] ANTIHYPERTENSIVE PRESCRIPTION PATTERNS AND CO-MORBIDITIES IN PATIENTS WITH NEWLY DIAGNOSED HYPERTENSION IN GERMANY. ANALYSIS OF GERMAN STATUTORY HEALTH INSURANCE DATA. (September 2017) - Limbourg, F.; Korzinek, A.; Haller, H.
Abstract : Objective: Inadequate treatment is one reason for poor hypertension control and prognosis in patients with hypertension. Guidelines recommend antihypertensive combination therapy for patients at increased risk or major co-morbidities. We analyzed antihypertensive prescription patterns and co-morbidities in patients with newly diagnosed hypertension. Design and method: In a database of several German statutory health insurance companies covering the period from 2011–2013 we analyzed the occurrence of newly diagnosed hypertension and major co-morbidities (diabetes, myocardial infarction, heart failure, stroke and renal dysfunction) by ICD code during 2012. We also analyzed the linked prescription data for antihypertensives by ATC code. Results: Of 2, 077, 889 persons at least 18 years of age, 32.2% carried the diagnosis hypertension, of which 7.9% (53, 118) were newly diagnosed in 2012 (incidence 2.6%). Newly diagnosed patients received antihypertensive medication in 78.2%, while 21.8% received none. 70.8% of the treated patients were initiated on monotherapy, 13.2% on combination therapy and 16.0% on fix-dose combination. In the monotherapy group, 43.5% received ACE inhibitors, 32.2% beta-blockers, 8.2% angiotensin II receptor blockers, 7.7% diuretics and 7.7% were prescribed calcium channel blockers. When free combination treatment was prescribed, 73.5% contained beta-blockers, 72.9% contained ACE inhibitors, 40.6% contained diuretics and 25.7% contained calcium channel blockers. Among newly diagnosed patients on monotherapy, 28.7% had at least one major co-morbidity, while in patients without antihypertensive treatment, at least one major co-morbidity existed in 18.0%. Conclusions: The majority of patients with newly diagnosed hypertension is initiated on monotherapy suitable for patients at low risk, while one fifth of patients remains untreated. However, in both groups a significant number of patients have at least one major co-morbidity, suggesting in part inadequate risk management.